2020
DOI: 10.3390/antibiotics9030113
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling and Pharmacodynamic Target Attainment Simulation of Piperacillin/Tazobactam for Dosing Optimization in Late Elderly Patients with Pneumonia

Abstract: The aim of this study was to develop a population pharmacokinetic model for piperacillin (PIPC)/tazobactam (TAZ) in late elderly patients with pneumonia and to optimize the administration planning by applying pharmacokinetic/pharmacodynamic (PK/PD) criteria. PIPC/TAZ (total dose of 2.25 or 4.5 g) was infused intravenously three times daily to Japanese patients over 75 years old. The plasma concentrations of PIPC and TAZ were determined using high-performance liquid chromatography and modeled using the NONMEM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Three piperacillin PK/PD targets are regularly used in the literature in critically ill patients:50% fT > MIC, 50% fT > 4 × MIC, and 100% fT > MIC [25,26]. When 50% ƒT > 4 × MIC of 16 mg/L was evaluated for piperacillin in consideration of conservative target, extended infusion of 4 g q6h could not achieve the desirable PTA in patients with CrCL > 20 mL/min; however, 50% fT > 16 mg/L re ects the worst-case associated with bacterial susceptibility in empirical treatment, and previous studies have shown these targets to be clinically meaningful [27].…”
Section: Discussionmentioning
confidence: 99%
“…Three piperacillin PK/PD targets are regularly used in the literature in critically ill patients:50% fT > MIC, 50% fT > 4 × MIC, and 100% fT > MIC [25,26]. When 50% ƒT > 4 × MIC of 16 mg/L was evaluated for piperacillin in consideration of conservative target, extended infusion of 4 g q6h could not achieve the desirable PTA in patients with CrCL > 20 mL/min; however, 50% fT > 16 mg/L re ects the worst-case associated with bacterial susceptibility in empirical treatment, and previous studies have shown these targets to be clinically meaningful [27].…”
Section: Discussionmentioning
confidence: 99%
“…S-ADAPT is based on the ADAPT package developed by D’Argenio, Wang and Schumitzky. Ishihara et al [ 40 ] and Soraluce et al [ 41 ] use the industry standard parametric version of NONMEM. Allard et al [ 42 ] uses the stochastic approximation expectation maximization method (SAEM).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Describing the PK of antimicrobials in the Asian population is important to determine dosing requirements for this population. Numerous countries in this region rely heavily on product information to guide antimicrobial dosing, which can potentially be flawed for critically ill patients [34][35][36]. Furthermore, dosing recommendations from the product information were mainly derived from dose-finding studies that mainly included subjects from non-Asian populations [37,38].…”
Section: Introductionmentioning
confidence: 99%